Transport properties of chemicals and hydrocarbons : viscosity, thermal conductivity, and diffusivity of C1 to C100 organics and Ac to Zr inorganics - Yaws, Carl L. (William Andrew, 2009)
Carl Yaws, a leading authority on chemical compounds in the chemical engineering field, has done it again. In Transport Properties of Chemicals and Hydrocarbons -- an essential volume for any chemist or chemical engineer's library -- he has amassed over 7,800 organic and inorganic chemicals, and hydrocarbons. Spanning gases, liquids and solids, and covering all critical properties (including viscosity, thermal conductivity, and diffusion coefficient), this volume represents more properties on more chemicals than any single work of its kind. From C1 to C100 organics and Ac to Zr inorganics, the data in this handbook was designed and formatted for field, lab or classroom usage. By collecting a massive amount of information in one source, this handbook will simplify your research and significantly reduce the amount of time that you spend collecting properties data. Chemical and process engineers, chemists, chemical engineering students, and anyone involved in process design, plant operations, R & D, industrial health and safety - and many other fields where finding properties data is important - will appreciate the unparalleled access to the invaluable data found in Transport Properties of Chemicals and Hydrocarbons.